Srategi Pemanfaatan Instagram Sebagai Media Periklanan - Saffanah Salma; Cecep Safa'atul Barkah; Tetty Herawaty; Lina Auliana (Faculty of Economics and Business University of Lampung, 2021)
This research aims to find out the right strategy in using Instagram as an advertising medium for MSMEs in Amoira using descriptive qualitative methods. The data is taken by doing two ways, namely interviews and also observations. The data obtained is processed by several methods such as internal resources analysis, Sustainable Competitive Advantage (SCA) analysis, VRIO framework, and also TOWS analysis. Then the researchers conducted a content analysis to propose strategies for using Instagram. In this study, generate strategies that can be carried out based on the analysis conducted on Amoira. Keywords: instagram utilization strategy, advertising media, impression Abstrak Penelitian ini bertujuan untuk mengatahui apa strategi yang tepat dalam pemanfaatan Instagram sebagai media periklanan pada UMKM Amoira menggunakan metode kualitatif deskriptif, data diambil dengan melakukan 2 cara yaitu wawancara dan juga observasi. Data yang diperoleh diolah dengan sejumlah metode seperti analisis internal resources, analisis Sustainable Competitive Advantage (SCA), framework VRIO dan juga analisis TOWS. Kemudian peneliti melakukan analisis konten untuk mengusulkan strategi pemanfaatan Instagram. Pada penelitian ini, menghasilkan strategi-strategi yang bisa dilakukan berdasarkan analisis yang dilakukan pada Amoira. Kata kunci: strategi pemanfaat instagram, media periklanan, impression